Early Childhood Development in Qatar : Status and Opportunities for the Future - Nikaein Towfighian, Samira (World Bank, Washington, DC, 2017)
Early childhood development (ECD) is a multidimensional process that takes place from conception until age five. These years mark the most important period for an individual's development. In this period, the building blocks of the brain and nervous system are formed, and critical skills and capacities begin to develop across a number of interrelated domains (Nelson 2000). Despite this ample international evidence, the state of ECD in Qatar has thus far been understudied. Child development outcomes in Qatar are below what is expected given its level of economic development. Gaps in self-regulation skills persist, with a third of children ages three and four being unable to attend to, and focus on, simple tasks without being distracted easily. As a tripartite collaboration between the World Innovation Summit for Education (WISE) at Qatar Foundation, the Ministry of Education and Higher Education of the State of Qatar and the World Bank, this study begins to fill this gap by providing an overview of the state of ECD in Qatar and setting forward recommendations to strengthen ECD in the country. The report first analyzes ECD outcomes in Qatar, examining how Qatar fares in five ECD domains compared to other countries. Section two builds the evidence base in the Qatari context by testing whether specific ECD programs are associated with improved child outcomes in the country. Section three takes a systemic view, analyzing the policies that govern ECD in Qatar and offers recommendations for their enhancement. Finally, section four concludes with a summary of key policy recommendations and some considerations for their implementation.